Design of a highly-extensible pneumatic actuator for soft robotic applications - Baydere, Bora Alp. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Soft continuum robots have been an expanding research topic due to their in herent compliance and ﬂexibility. However, most of the conventional continuum robots still lack the ability to signiﬁcantly change size and length. In this study, a novel highly-extensible pneumatic actuator is developed that can help overcome the limited extension capabilities of soft continuum robots. The main advantage of the actuator is that extension is directly controlled by an external motor, independent from pressure. First, models are given to calculate actuator force, speed and stiﬀness. A prototype of the actuator is manufactured, and experiments are performed to validate the model. Second, a soft robot is designed using the proposed actuator that can achieve controlled extension and active steering of the tip. Two prototypes are developed; one that can move on a plane and one that can move in 3D space. Finally, the robots are tested to explore their mechanical characteristics and navigation capabilities in free space, through obstacles and in enclosed environments. The results indicate that multiple actuators can be used to successfully navigate a tip-extending soft continuum robot. Speed test results show that controlling actuator speed independent from pressure is possible with the proposed actuator.
Keywords: Robots.